Single-incision laparoscopic cholecystectomy: Single institution experience and literature review - Hirano, Yasumitsu (Baishideng, 2010)
Single-incision laparoscopic surgery is a rapidly evolving field as a bridge between traditional laparoscopic surgery and natural orifice transluminal endoscopic surgery. We report one of the initial clinical experiences in Japan with this new technique. Four cases of gallbladder diseases were selected for this new technique. A single curved intra-umbilical 25-mm incision was made by pulling out the umbilicus. A 12-mm trocar was placed through an open approach, and the abdominal cavity was explored with a 10-mm semi-flexible laparoscope. Two 5-mm ports were inserted laterally from the laparoscope port. A 2-mm mini-loop retractor was inserted to retract the fundus of the gallbladder. Dissection was performed using an electric cautery hook and an Endograsper roticulator. There were two women and two men with a mean age of 50.5 years (range: 40-61 years). All procedures were completed successfully without any perioperative complications. In all cases, there was no need to extend the skin incision. Average operative time was 88.8 min. Postoperative follow-up didnot reveal any umbilical wound complication. Single-incision laparoscopic cholecystectomy is feasible and a promising alternative method as scarless abdominal surgery for the treatment of some patients with gallbladder disease.